2022
DOI: 10.1523/eneuro.0361-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Evidence for Cognitive Map Formation during Sequence Learning

Abstract: Humans deftly parse statistics from sequences. Some theories posit that humans learn these statistics by forming cognitive maps, or underlying representations of the latent space which links items in the sequence. Here, an item in the sequence is a node, and the probability of transitioning between two items is an edge. Sequences can then be generated from walks through the latent space, with different spaces giving rise to different sequence statistics. Individual or group differences in sequence learning can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 106 publications
(177 reference statements)
1
17
0
Order By: Relevance
“…Second, we assume that knowledge networks are embedded in Euclidean space, where they possess several degrees of freedom. Both assumptions are predicated on how humans encode spatial and abstract knowledge (Garvert et al, 2017; Peer et al, 2021; Stiso et al, 2022; Warren, 2019). Evidence from spatial navigation studies demonstrates that mental representations of space take the form of labeled cognitive graphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we assume that knowledge networks are embedded in Euclidean space, where they possess several degrees of freedom. Both assumptions are predicated on how humans encode spatial and abstract knowledge (Garvert et al, 2017; Peer et al, 2021; Stiso et al, 2022; Warren, 2019). Evidence from spatial navigation studies demonstrates that mental representations of space take the form of labeled cognitive graphs.…”
Section: Discussionmentioning
confidence: 99%
“…One such model that has shown promise is a network model where knowledge is composed of discrete and yet interconnected concepts (Chrastil and Warren, 2014, 2015; Ericson and Warren, 2020; Peer et al, 2021; Schapiro et al, 2016; Stiso et al, 2022; Warren et al, 2017). In graph learning studies, volunteers are shown sequences of images on a screen, where, unbeknownst to the volunteers, each image corresponds to a node in an underlying network (Lynn and Bassett, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we assume that knowledge networks are embedded in Euclidean space, where they possess several degrees of freedom. Both assumptions are predicated on how humans encode spatial and abstract knowledge [23,24,27,54]. Evidence from spatial navigation studies demonstrates that mental representations of space take the form of labeled cognitive graphs.…”
Section: Discussionmentioning
confidence: 99%
“…One such model that has shown promise is a network model where knowledge is composed of discrete and yet interconnected concepts [18,19,20,21,22,23,24]. In graph learning studies, volunteers are shown sequences of images on a screen, where, unbeknownst to the volunteers, each image corresponds to a node in an underlying network [25].…”
Section: Introductionmentioning
confidence: 99%
“…For navigation‐based sequence learning in rodents, the hippocampus has been shown to be involved in learning sequences of places (Foster & Knierim, 2012), and is recruited during sequence‐based navigation, but not during exploration behavior (Babayan et al, 2017). Further, a recent study using human intercranial electroencephalographic recordings showed that neural activity elicited by non‐spatial sequence learning closely resembled that predicted by neural models of cognitive map formation, most strongly in the hippocampus (Stiso et al, 2022). In fact, aging adults (both healthy and those showing cognitive decline) often experience marked volumetric decline and structural changes to the hippocampus (Bettio et al, 2017), which coincides with difficulties in spatial sequence learning and cognitive map‐reliant navigation in these populations (Lester et al, 2017).…”
Section: Introductionmentioning
confidence: 87%